Teknik penerjemahan ungkapan sindiran pada subtitle serial televisi Netflix: Bridgerton - Dwita Darmawati; Sajarwa Sajarwa (Aksara: Jurnal Bahasa dan Sastra, 2021)
This article is a descriptive qualitative study. The aims of this study are to identify types of satirical expression and identify the translation techniques used to translate the satirical expression found in serial television subtitle entitled ‘Bridgerton’. The utterance contains satirical expression found in 5 episodes of the serial television used as data in this research—the data obtained through content analysis. There are four types of satirical expression analyzed in this research; irony, satire, cynicism and sarcasm. Furthermore, the result suggests that there are 66 data of satire, 49 data of cynicism, 29 data of sarcasm, and 27 data of irony. On the other hand, there are 13 translation techniques applied in translating the utterance of satirical expression. The most dominant technique used is reduction (29) followed by discursive creation (23), established equivalent (23), literal translation (22), compensation (21), linguistic compression (20), transposition (14), modulation (8), linguistic amplification (4), borrowing (3), particularization (2), adaptation (1), dan substitution (1). The use of reduction technique is to shorten the subtitles that appear on the screen. Keywords: satirical expression, translation techniques, subtitle, serial television.